Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fpls.2023.1114852
|View full text |Cite
|
Sign up to set email alerts
|

UAV imagery data and machine learning: A driving merger for predictive analysis of qualitative yield in sugarcane

Abstract: Predicting sugarcane yield by quality allows stakeholders from research centers to industries to decide on the precise time and place to harvest a product on the field; hence, it can streamline workflow while leveling up the cost-effectiveness of full-scale production. °Brix and Purity can offer significant and reliable indicators of high-quality raw material for industrial processing for food and fuel. However, their analysis in a relevant laboratory can be costly, time-consuming, and not scalable. We, theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that sugarcane yield parameters such as tiller number, plant height, and stalks could be efficiently estimated using UAV LIDAR and UAV multispectral image data for accurate plot scale sugarcane yield estimation [7][8][9]. Akbarian et al [10] and Barbosa-Júnior et al [11] examined the combination of multispectral UAV imagery with several machine learning methods for plot-scale sugarcane yields estimation and showed that the random forest algorithm had the best accuracy for the estimation. Though these studies demonstrated the possibility of accurate plot-scale estimation of sugarcane yield and production, problems such as workload reduction, lossless sampling, and fast and accurate estimation are still remained as challenges which required effective solutions [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that sugarcane yield parameters such as tiller number, plant height, and stalks could be efficiently estimated using UAV LIDAR and UAV multispectral image data for accurate plot scale sugarcane yield estimation [7][8][9]. Akbarian et al [10] and Barbosa-Júnior et al [11] examined the combination of multispectral UAV imagery with several machine learning methods for plot-scale sugarcane yields estimation and showed that the random forest algorithm had the best accuracy for the estimation. Though these studies demonstrated the possibility of accurate plot-scale estimation of sugarcane yield and production, problems such as workload reduction, lossless sampling, and fast and accurate estimation are still remained as challenges which required effective solutions [6,10].…”
Section: Introductionmentioning
confidence: 99%